Determination of the range of angular velocities of the auto-balancing mode for a vertical rotor system with a Leblanc-type balancer - Drach, Ilona; Dykha, Oleksandr; Matiukh, Serhii; Dykha, Maksym (Eastern-European Journal of Enterprise Technologies, 2025)
Automatic balancing devices (ABDs) of the Leblanc type – passive ABDs of the liquid type – are used in rotary machines to reduce their vibration level when the distribution of masses around the geometric axis of rotation changes during machine operation or during its restart. To redistribute the masses during balancing, the movement of the working (correcting) liquid in the direction opposite to the imbalance is used. The object of this study is the motion modes (qualitative states) of the working liquid in the chamber of the balancing device for the vertical rotor system. The study is aimed at substantiating the existence of the auto-balancing mode at subcritical angular velocities of the rotor system and investigating its conditions and features. This paper reports the results of modeling the motion modes of the working liquid in the cylindrical chamber of the Leblanc ABP at a subcritical range of rotation speeds taking into account the vector relationships of the force factors depending on the design parameters of the auto-balancing device, the volume of the working fluid, and the shape of its free surface. Estimates of the angular velocities of switching on the working liquid under the rotational motion and under the auto-balancing mode have been analytically and experimentally substantiated, constituting, respectively, 1/3 and 1/2 of the critical angular velocities of the rotor system. For the practice of balancing an elastically deformable rotor and a rotor on elastic supports, the results of the study expand the range of rotation speeds where the balancing of the imbalance by the liquid and the reduction of the amplitudes of vibration processes are observed. This could help increase the service life, reliability, and accuracy of the technological process of machines with variable rotor imbalance by monitoring their vibration resistance through the use of liquid ABDs